A comparative study of low dose magnesium sulphate (Dhaka regime) and Pritchard regime for the management of impending eclampsia and eclampsia - Ranjana, .; Sinha, Abha Rani; Prakash, Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is a common obstetrical emergency though preventable, yet remains a leading cause of maternal and perinatal morbidity and mortality in the developing world. Pritchard regime is most widely used magnesium sulphate regime for control of eclamptic fits but its dose related toxicity is a major concern among Indian women with low BMI and at peripheral institutions where the patients monitoring is limited. The objective was to study the efficacy of low dose MgSO4 regime (Dhaka regime) for control of convulsions in eclampsia and prevention of convulsions in impending eclampsia, to assess the magnesium related toxicity and to analyze the maternal and perinatal outcomes as compared to standard Pritchard regime. Methods: This prospective study was carried out in the Department of obstetrics and Gynaecology at Patna Medical College and Hospital, Patna. Study was done on 80 patients of eclampsia and impending eclampsia. Patients were divided into two groups A and B. Group A (n=40) received low dose MgSO4 regime (Dhaka regime) and Group B (n=40) received standard Pritchard regime. Results were analysed using statistical package of social sciences (SPSS) 21.0. Statistical significance was set at p ≤0.05. Results: In the present study, convulsions were controlled in 95% of eclampsia cases with low dose magnesium sulphate (Dhaka) regime. Recurrence of convulsion was seen in both groups. None of the patients with impending eclampsia in both the groups developed the seizure during entire treatment period. Signs of impending MgSO4 toxicity and the mean amount of magnesium sulphate received was found more in Pritchard regime group (22.5gms in Group A and 39gms in Group B) and was statistically significant with p value <0.001. There were 3 maternal deaths in present study. Conclusions: Low dose magnesium sulphate is as effective as standard Pritchard regime in controlling the eclamptic fits and preventing its recurrence with comparable maternal and perinatal outcome and less chances of magnesium toxicity. This regimen may be more suitable for use in Indian women with low BMI and in resource poor settings where clinical monitoring is limited.